PerLA: A thermo-hydro-mechanical framework coupling land–atmosphere interactions for evaluating highway and railway subgrade performance in permafrost regions - Jiaming Ye; Ruiqiang Bai; Weipeng Xu; Tianju Xue; Limin Zhang (Computers and Geotechnics, 2027)

Interpretable mapping of fine-grained urban building functions from street-view images using foundation models - Jiaming Sun; Wei Yang; Tingting Xu; Zongshun Tian; Yongchuan Zhang; Mengjia Yin (Computers, Environment and Urban Systems, 2026)

Integrative genetic analysis reveals shared genetic architecture underlying coronary artery disease, CT-Defined coronary atherosclerosis, and cardiometabolic risk factors - Yao Zhao; Yingying Xie; Didi Wen; Jin Zhang; Ziliang Xu; Zhibin Wu; Jiaming Li; Yuanqiang Zhu; Minwen Zheng (Functional & Integrative Genomics, 2026)

A kidney-targeted MOF nanozyme combats calcium oxalate crystal-induced kidney injury - Xuhong He; Min Zhou; Zhengxin Liang; Shiyi Jin; Kunze Yu; Longxiyu Meng; Zhicong Tan; Jinming Xu; Jiaju Xu; Chongjun Xiang; Jingchao Wei; Wenjun Gao; et al. (Chemical Engineering Journal, 2026)

Time-resolved volatile profiles and molecular-species lipid remodeling during lipase treatment of anhydrous milk fat - Anqi Chen; Qingyun Xu; Jiaming Li; Yanxi Chen; Qiance Shen; Guocheng Du; Jianghua Li; Jian Chen (Food Research International, 2026)

Thermally regenerable zwitterionic metal-organic frameworks with proton transfer properties for efficient lithium extraction - Xu Wu; Qian Guan; Mengyu Tang; Yue Zheng; Zhipeng Luo; Qiuyue Liu; Jiaming Gan; Xin Yu; Ranwen Ou (Chemical Engineering Journal, 2026)

Microalgae-based biogas slurry treatment integrated with sustainable aviation fuel production: from waste to high-value bio-jet fuel - Binbin Zhu; Hongyin Chen; Jing Lv; Wenjun Zhang; Jiaming Liu; Ruirui Liu; Bishu Qi; Shuhui Li; Chengyu Yang; Xiao Yan; Zijian Xia; Xingliang Xu; et al. (Bioresource Technology, 2026)

Nickel from olivine dissolution induces diel photodamage and metabolic adjustment in Gracilariopsis lemaneiformis - Chang Liu; Dong Xu; Xuewei Wang; Yiqun Wu; Yuan Chang; Jiaming Zhang; Xinyu Qian; Ling Liu; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2026)

Selective infrared thermal modulation device based on mixed-crystalline WO3 and electrochromic dynamic regulation technology - Jiaming Yang; Mengying Wang; Abderaouf DJEFFAL; Shukai Wang; Zheng Meng; Xinru Xu; Xungang Diao (Chemical Engineering Journal, 2026)

Abscisic acid promotes watercore dissipation by accelerating sorbitol decomposition through the MdNAC25-MdSDH8 module in apple fruit - Yali Li; Hao Wei; Qian Ma; Jiaming Li; Zuanhong Xu; Yamei Ren; Xiaolin Ren; Yuduan Ding (Postharvest Biology and Technology, 2026)

3D laser scanning-based geometry reconstruction and stress evaluation of a KK-type cast steel node for offshore wind turbine jacket structures - Feng Shi; Hui Jin; Lu Xu; Jiaming Liu; Jiahao Hu; Haihan Jiao (Ocean Engineering, 2026)

Humic acid-mediated activation of antimony colloid during soil redox cycles: Mechanisms and environmental implications - Xiongkai Zheng; Jiaming Xu; Haiming Cai; Qiming Mo; Yihao Li; Qixian Fu; Lijuan Zeng; Yongyang Wang; Xueqin Tao; Zhi Dang; Guining Lu (Journal of Hazardous Materials, 2026)

Targeted “ROS storm” in hypoxic periodontitis: A self-enhanced SDT/CDT synergistic platform based on triple-enzymatic Cu-Mo bimetallic nanozyme - Wei Wu; Tong Xu; Kehan Wu; Lilong Yang; Jiaming Wang; Kaidi Liang; Dan Yang; Piaoping Yang; Narisu Hu (Chemical Engineering Journal, 2026)

A novel LSTM-Kriging model for spatiotemporal interpolation of air pollution - Rui Xu; Jiaming Zou; Yuanfeng Sun; Jian Li; Liyi Guo; Shiming Shen; Hang Wan (Air Quality, Atmosphere & Health, 2026)

Two-terminal ferroelectric memristors: material innovation, mechanistic breakthroughs, new opportunities for intelligent computing - Jiaming Zhang; Chaocheng Sun; Yan Jing; Yifei Pei; Jianbin Xu; Xiaobing Yan; Jianhui Zhao (Science Bulletin, 2026)

Gibberellic acid modulated ethylene, ascorbate-glutathione cycle, and fatty acid metabolism to attenuate the browning of watercore apple fruit: Insights from transcriptomic evidence - Yali Li; Hao Wei; Yunya Zhao; Jiaming Li; Zuanhong Xu; Changhao Song; Yamei Ren; Xiaolin Ren; Yuduan Ding (Postharvest Biology and Technology, 2026)

Generalized traverse task scheduling based on THRO algorithm for AUV with energy-constrained - Qixin Sha; Rui Nian; Jiaming Zhang; Xiaoting Xu; Yue Shen; Bo He (Ocean Engineering, 2026)

P300-mediated H3K56la delactylation promotes copper-induced steroidogenesis disorders in human ovarian granulosa cells - Panlin Wang; Jiaming Xiao; Bingbing Wang; Yi Zhang; Ke Xu; Yingjie Dou; Qianqian Guo; Ye He; Yan Sun; Wenxiang Wang (Journal of Hazardous Materials, 2026)

A novel multifunctional bacterial consortium synergistically promotes rhizoremediation of dibutyl phthalate and cucumber growth: Insights from multi-omics analyses - Jiaming Xu; Yan Li; Haoyan Han; Yi Wu; Yue Tao; Yuexuan Ma; Zhao Jiang; Ying Zhang (Journal of Environmental Sciences, 2026)

Geometry-dependent nonlinear flow behavior in mortar replicas with a single rough mismatched fracture - Xunhui Xu; Weiren Lin; Jiaming Zhu (International Journal of Rock Mechanics and Mining Sciences, 2026)

In-situ sulfur element-induced heterogeneous interface engineering for high-performance supercapacitors - Mingzhe Shan; Yi Jiang; Ruixiang Xu; Bin Cai; Yi Gao; Heju Zhao; Jiaming Wang; Yaozeng Lu; Xiqing Song; Surong Tan; Yishan Yuan; Zining Li; et al. (Chemical Engineering Journal, 2026)

Assessment of laterization degree of tropical residual laterites overlying carbonate rocks in Yunnan, China - Haiyan Gao; Zhongxin Deng; Zemin Xu; Yixi Wen; Jiaming Zhang; Jipu Chen; Lin Tian (CATENA, 2026)

Quantifying tire wear particle dynamics: insights from a hydrological-based material flow analysis in urban watersheds - Lebing Ying; Shujie Xu; Jiaming Wang; Shu-Chien Hsu (Journal of Industrial Ecology, 2026)
Tire wear particles (TWPs) constitute a significant fraction of total microplastic release, necessitating quantification for effective management. While material flow analysis (MFA) quantifies their pathways from generation to environmental sinks, existing approaches apply uniform transfer coefficients across entire regions, obscuring critical spatial heterogeneity essential for assessing ecosystem exposure. This study developed a spatially explicit, process-based MFA framework by integrating mechanistic TWP generation modeling with hydrological rainfall-runoff processes to quantify TWP generation, road surface accumulation, and storm-driven mobilization in Hong Kong. Results indicate an annual per capita TWP generation of 0.28 kg/person/year, notably lower than the global average. Over half of the generated TWPs were mobilized by stormwater runoff after road surface deposition. The hydrological transport pathway to surface water exhibits pronounced spatial and event-driven heterogeneity. Spatially, while suburban districts with extensive road networks dominated absolute emissions (24%), dense urban cores exhibited generation intensities 15 times higher and washoff intensities 18 times greater than outlying low-density areas. In terms of event dynamics, storm-event modeling demonstrates that extreme precipitation following prolonged dry periods can mobilize 30% of annual TWP loads within 24 h, fundamentally reorganizing pollution distributions. This framework provides a transferable tool for pinpointing TWP hotspots and informing targeted mitigation strategies in urban watersheds worldwide.

Evaluation of Groundwater Origin, Quality, and Potential Health Risks in the Ordos Coal Mine Base, Northwest China: Insights from Geochemical and Isotopic Approaches - Jiaming Zhou; Keyi Zhang; Tenglin Deng; Zilong Liao; Bing Xu; Fei Gao; Quandong Lian; Jianghong Yan; Shen Qu (Mine Water and the Environment, 2026)

Morphology–aware spatiotemporal prediction of cumulonimbus–related radar echoes using CSDP–Net - Deyi Wang; Xu Wang; Zhenhong Cheng; Xin Chang; Hongping Yuan; Jixiang Yang; Yi Liang; Jiaming Hu; Ting Zhang (Theoretical and Applied Climatology, 2026)

Research on the Support Mechanism of Tunnel Anchor Bolt Based on Physical Model Experiments and Continuous–Discontinuous Theory - Mingyi Wang; Shaobo Chai; Bo Hu; Chen Xu; Jiaming Wu; Yongqiang Zhou; Xiaodong Fu (Rock Mechanics and Rock Engineering, 2026)

Optimization design research of vibration control parameters for Submerged Floating Tunnel based on GA-AIF-PSO algorithm - Jiaming Xie; Jianyun Chen; Ning Su; Jing Li; Qiang Xu (Ocean Engineering, 2026)

Mechanical behavior of marine coral sand - coral clay mixtures reinforced with bionic honeycomb polymer grid: Experimental and artificial intelligence methods - Kaiwei Xu; Jiaqi Luo; Jiaming Zhao; Danda Shi; Zhiming Chao; Titi Sui (Ocean Engineering, 2026)

Cerium-modified Cu-SSZ-13 catalysts: Enhanced low-temperature activity and hydrothermal stability for efficient NOx reduction - Bin Guan; Kaiyou Shu; Lei Zhu; Tiankui Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Hongtao Dang; Luyang Zhang; et al. (Journal of Environmental Chemical Engineering, 2026)

Multi-membrane integrated process enables efficient electrodialytic separation of alkaloids from aqueous extract of Caulis sinomenii - Lanlan Zhang; Xixi Ma; Tingting Xu; Shanshan Liu; Luna Chen; Jiaming Ji; Jinfeng He; Li Sun; Xiaocheng Lin; Chuanrun Li; Haiyang Yan (Desalination, 2026)

Circadian Rhythm Disorder-Related Dysfunctions are Exacerbated by Aging and Ameliorated by Time-Restricted Feeding - Fengjiao Huo; Qing Liu; Shuaishuai Zhang; Xiaorui Liu; Shuyao Lv; Meili Zhao; Yue Liu; Xiaoqi Zhu; Ce Huang; Shengyu Feng; Hao Wang; Siling Xu; et al. (Neuroscience Bulletin, 2026)

Influence of interface flow field on slope deterioration mechanism under freeze–thaw cycles: insights from physical model testing - Jiaming Zhang; Hao Xu; Xingyu Gao; Teng Liang; Xuecheng Bian (Transportation Geotechnics, 2026)

Research on emission control performance of SSCR system based on multi-condition operation and three-high tests - Bin Guan; Kaiyou Shu; Lei Zhu; Tiankui Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Hongtao Dang; Luyang Zhang; et al. (Fuel, 2026)

Side-deep placement of controlled-release urea combined with alternate wetting and drying irrigation achieves sustainable intensification of rice production in the rice–wheat system - Yuan Wang; Li Zhang; Kai Ming; Lin Cao; Song Guo; Jiaming Lu; Ziwei Li; Weiling Wang; Can Zhao; Fengping Yang; Ke Xu; Hongcheng Zhang; et al. (Field Crops Research, 2026)

Localized chemotherapy through metabolic stabilization and in situ gelation for ratio-locked delivery to maximize cytotoxicity and trigger immune responses - Jiaming Zhang; Xinyu Lou; Xiaolan Xu; Yingchao Li; Chenxia Bai; Qing Yan; Yanfang Wang; Yixiu Zhai; Jingdong Xiao; Mengchi Sun; Yinghou Wang; Jin Sun; et al. (Chemical Engineering Journal, 2026)

Prediction of Heterogeneous Shale Lithology in the Kaijiang–Liangping Trough Based on Dream Optimization Algorithm and Support Vector Machine - Lexin Yuan; Zhiming Xu; Haofei Sun; Jungang Lu; Luchuan Zhang; Xiangdong Yin; Jiaming Li (Mathematical Geosciences, 2026)

The role of ammonia in the global energy transition: opportunities and challenges in ammonia gas turbine technology - Shuai Chen; Bin Guan; Lei Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Kaiyou Shu; Hongtao Dang; Luyang Zhang; et al. (Fuel, 2026)

High-efficiency catalytic removal of N2O from ammonia-fueled engine exhaust - Bin Guan; Zhongqi Zhuang; Lei Zhu; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Kaiyou Shu; Hongtao Dang; Luyang Zhang; Tiankui Zhu; et al. (Fuel, 2026)

Biomimetic tactile sensor for dynamic-static perception based on piezoionic and piezoresistive effects - Huanyu Liu; Jiaming Fan; Yongqi Kuang; Jing Xu; Qizhao Liang; Zhimeng Liu; Jun-Wei Zha; Yunhui Wu (Chemical Engineering Journal, 2026)

Low-cost, scalable fabrication of antibacterial asymmetric hydrogels inspired by mangrove systems for superior oil-water separation and salt-tolerant evaporation - Qidong Zha; Zuozhu Yin; Yingping Yang; Guoyan Yang; Jiaming Ni; Jilin Xu; Zhen Hong; Chan Xie; Yidan Luo; Mingshan Xue (Water Research, 2026)

Evaluating aeration rate modulation to restructure denitrifier communities for nitrous oxide mitigation in cattle manure composting using a novel integrated analytical framework - Yu Sun; Xiran Zhou; Jiaming Fan; Lei Sun; Shuai Shi; Xiuhong Xu (Journal of Environmental Management, 2026)

Development of a modified CaCl2·6H2O shape-stabilized composite phase change material for the greenhouse soil-cooling system - Fuyu Qin; Runhua He; Lingzhi Zhong; Tao Xu; Jiaming Gao; Ximin Lin; Yi Yang; Weitao Shao (Energy and Buildings, 2026)

Unlocking ultrahigh anion adsorption in sunlight-responsive metal-organic frameworks for water purification - Xu Wu; Qian Guan; Mengyu Tang; Yilei Fang; Jiaming Gan; Xinyu Zhang; Xin Yu; Ranwen Ou (Chemical Engineering Journal, 2026)

Ionic liquid-derived fluorine doped high entropy metal oxides as efficient electrocatalysts for sulfion valorization - Longmei Shi; Anshuang Wu; Shengyun Xu; Jinbiao Liang; Shucan Qin; Jiaming Mao; Yanrong Liu; Yunqian Ma (Journal of Environmental Chemical Engineering, 2025)

Thermophilic antagonistic/competitive networks drive low nitrogen loss in Phase I commercial composting: Deciphering microbe-nitrogen coupling using the novel multistep interaction validation analysis - Yu Sun; Jiaming Fan; Yue Zhang; Zhaoxue Gai; Shuai Shi; Xiuhong Xu (Journal of Environmental Chemical Engineering, 2025)

Fiber-regulated vibration suppression and mechanical behavior of CFRP corrugated channel cored sandwich structures - Jiaming Sun; Yanlong Xu; Keyu Zhu; Leilei Yan; Xitao Zheng; Zhichun Yang (Engineering Structures, 2025)

Machine learning-driven design for globally optimal performance of flexible pressure sensors - Yuhan Zhao; Zhanfeng Guo; Zetian Zhao; Hengbin Ding; Xiaoshi Li; Yihan Xu; Daixuan Wu; Zhongheng Sun; Yifan Li; Jiaming Li; Ruolan Zhao; Minghao Wang; et al. (Chemical Engineering Journal, 2025)

The effect of hydroxyl groups and humidity on the adsorption capacity of amine-functionalized macroporous resins for direct air capture - Jiaming Wang; Xiaohan Weng; Tao Han; Yongqiang Wang; Jinning Yang; Chao Zhou; Dong Xu; Liying Liu (Chemical Engineering Journal, 2025)

Unveiling spatiotemporal patterns of urban ecosystem services flows in urban thermal environments: Insights from residency, age, and gender disparities - Jiaming Yang; Zhaomin Tong; Yaolin Liu; Yanfang Liu; Jiwei Xu; Yanchi Lu; Yifan Xie; Yang liu (Sustainable Cities and Society, 2025)

Transcriptomic and metabolomic analysis reveals the effect of hydrogen sulfide on delaying fruit ripening and color transition of white fleshed strawberry (Fragaria ananassa) - Miao Sun; Yue Wen; Xuanhuan Qiao; Tao Yang; Peng Zhao; Junhao Zhao; Jiaming Luo; Jialun Zhang; Zhipeng Zhu; Weijian Cai; Meng Xu; Li Yao; et al. (Postharvest Biology and Technology, 2025)

Stable precursor-ink strategy for inkjet-printed high-temperature oxide films: Towards scalable ITO/In2O3 fabrication - Bian Tian; Jiaming Lei; Zhongkai Zhang; Yedi Zhou; Heng Li; Meng Wang; Shuimin Li; Xu Fan; Guoliang Zhou; Zhaojun Liu; Peng Shi (Chemical Engineering Journal, 2025)

Adipose-derived soluble fractions activated bioink promotes cutaneous repair and regeneration via mobilizing endogenous reparative cells - Wei Zhang; Jiaming Shao; Hanlei Zhou; Min Yang; Chenghao Cai; Fang He; Yiran Wang; Pengqin Xu; Sizhan Xia; Tingting Weng; Jialiang Wang; Ronghua Jin; et al. (Chemical Engineering Journal, 2025)

Metabolic Control of Stem Cell Function: Insights into Amino Acid-Driven Mechanisms - Jiawei Zeng; Xiaohao Liu; Jiaming Bi; Chuzi Mo; Han Zhang; Yan Chai; Yunhe Lin; Siwei Li; Zhongjun Liu; Mingyan Yao; Shuaimei Xu; Peiyan Yuan (Stem Cell Reviews and Reports, 2025)

Recycling waste poly(ethylene terephthalate) to prepare a Zn–MOF and its application as a nucleating agent for plastics and antibacterial agent on cotton fabrics - Xiaohui Lin; Jiaming Xu; Guoliang Sun; Jingjing Sun; Yi Xiao; Yanling Hu; Jinqing Yang; Yubiao Liao; Jianchun Liu; Mingyi Shang; Kun Wu (Journal of Environmental Chemical Engineering, 2025)

Improving storage stability of dairy emulsions via xanthan gum and carboxymethyl cellulose synergy - Qingyun Xu; Jiaming Li; Fanjun Meng; Yanfang Sun; Xuexian Du; Yingle Wu; Jianguo Yan; Jian Chen; Anqi Chen; Jianghua Li (Food Bioscience, 2025)

Fe/Mo synergistic confinement in controlled N-doped carbon nanotubes frameworks: Multiscale insights and octogen degradation in multisolvent systems–performance, interfacial mechanisms, and electronic optimization - Junlan Tang; Jinmao Ma; Panpan Zhou; Jihui Zhang; Xiaojun Wang; Yuqian Shi; Jiaming Xu; Xiangru Zhou; Yuling Bai; Jiade Lin; Chi Chen; Lincheng Zhou; et al. (Chemical Engineering Journal, 2025)

Differential ecotoxicity of nanoencapsulated metamifop and its active ingredient in zebrafish (Danio rerio): Insights from transcriptome and metabolome analysis - Yujun Xu; Simin Yu; Jiaming Yin; Zeng Wang; Jie Shen; Shaowen Liu; Xile Deng; Shuo Yan (Pesticide Biochemistry and Physiology, 2025)

Investigation on hydraulic conductivity reduction for silty sand by enzyme induced calcium carbonate precipitation considering urease activity and cementing solution concentration - Lei Shi; Liuhui Huo; Jiaming Fang; Xiangchun Xu; Jianwei Zhang (Engineering Geology, 2025)

Efficient separation and recycling of waste wind turbine blades through in-situ generation of peroxyacetic acid - Xinyi Xu; Jiaming Liu; Jiachun Feng; Bin Chen; Shiwen Gong; Xueer Ouyang; Changxu Qin; Gang Luo; Shicheng Zhang (Resources, Conservation and Recycling, 2025)

Enhancing ecological risk assessment of dioxins in aquatic environments: AHR diversity and species sensitivity differences in tiger puffer (Takifugu rubripes) - Zhenhong Xue; Wanglong Zhang; Anran Ren; Sibel I. Karchner; Diana G. Franks; Yanjiao Zong; Yongchao Ma; Jiayi Wang; Yiqin Xu; Jiaming Li; Ning Ding; Chunchen Liu; et al. (Journal of Hazardous Materials, 2025)

Water quality prediction at large-Scale: Systematic assessment of decomposition-deep learning models - Jiahui Shi; Lixiao Ni; Jiaming Liu; Hui Chen; Yushen Ma; Yi Zhang; Qingwei Lin; Zhen Zhang; Hang Xu; Yiping Li (Journal of Cleaner Production, 2025)

Fabrication of multifunctional sandwich-structured electrospun magnetic film for preventing postoperative recurrence of hepatocellular carcinoma and abdominal adhesions - Rui Wang; Xuanxuan Li; Liang Yan; Jinlong Hu; Haojie Lu; Jiaming Yao; Zhongxu Yuan; Jinshan Liu; Hongyu Xu; Xu Yan; Wenyong Wu; Baoqiang Cao (Chemical Engineering Journal, 2025)

Efficient and anti-interference plastic classification method suitable for one-shot learning based on laser induced breakdown spectroscopy - Zhiying Xu; Xingyu Zhao; Xinying Peng; Kai Wang; Kedong Wang; Nan Zhao; Jiaming Li; Qingmao Zhang; Xueqing Yan; Kun Zhu (Chemosphere, 2025)

Study on hot spot stress distribution and fatigue life assessment of KK-type cast steel nodes based on scaled model test - Haihan Jiao; Jiaming Liu; Lu Xu; Feng Shi; Hui Jin; Yongchun Fan (Ocean Engineering, 2025)

Study on the division method of the excavation disturbed zone in tunnels based on continuous-discontinuous theory - Jixu Zhang; Xiaodong Fu; Chao Tan; Yongqiang Zhou; Qian Sheng; Chen Xu; Jiaming Wu (Bulletin of Engineering Geology and the Environment, 2025)

Oxidation mechanisms of ammonia and ethanol mixed fuel by using the ReaxFF-MD simulation - Chongchong She; Chunchen Xu; Jiaming Gao; Zhi Wang; Shaohua Jin; Lijie Li; Junfeng Wang; Liang Song; Pengwan Chen; Kun Chen (Fuel, 2025)

The promotion mechanism of ammonia-based CO2 capture by hydroxyl and amine additives: A molecular dynamics and DFT study - Jiaxing Du; Wu Yang; Linlin Xu; Jiaming Chen; Zijian Song; Ben Wang; Lushi Sun (Fuel, 2025)

Associations of wildfire-derived particulate matter with hospitalization, emergency department visits and mortality: A systematic review and meta-analysis - Yiyi Wang; Jie Chen; Yujia Huang; Jiaming Wang; Yi Xiong; Tao Xue; Xu Yue; Fuping Qian; Meng Wang (Environmental Research, 2025)

Near-white light-emitting copper nanoclusters/starch composites for multiplexing imaging and multichannel enhancement of latent fingerprints - Zhibo Gao; Chuanjun Yuan; Ming Li; Zhize Xu; Meng Wang; Jiaming Lyu; Shiqiang Sun; Fenghe Liu; Peiliang Han (Chemical Engineering Journal, 2025)

Unmet needs of patients with intravascular large B-cell lymphoma: three case reports and a literature review - Xian Li; Ru Luo; Jiaming Xu; Xueli Jin; Weiqin Wang; Xibin Xiao; Wenbin Qian (Journal of Zhejiang University-SCIENCE B, 2025)

ADAM17 promotes colorectal cancer migration and invasion by regulating the TGF-β/Smad signaling pathway - Jiaming Li; Tingjin Zheng; Yingzhi Xu; Mengcha Tian; Liangpan Shi; Jintu Chen; Tian Li; Zhishan Zhang (Tissue and Cell, 2025)

Ternary Fenton-like material (γ-Fe2O3/MoS2/PANI) supported on polysulfate membrane for high-performance catalytic degradation of tetracycline solution - Jiaming Xu; Heng Zhang; Lian-Biao Zhao; Xiaohong Xing; Junlan Tang; Xiangru Zhou; Lincheng Zhou (Journal of Water Process Engineering, 2025)

Dual redox-centered p(thiophene-TPA) conjugated polymers for high-performance flexible electrochromic supercapacitors - Xu Cheng; Chunhui Du; Jiaming Li; Yuqiao Zhang; Wenyuan Xu; Jianming Zhang; Hui Shi; Ge Zhang; Long Zhang (Chemical Engineering Journal, 2025)

Correction: Human Bone Marrow Mesenchymal Stem Cell–Derived Exosomes Attenuate Blood–Spinal Cord Barrier Disruption via the TIMP2/MMP Pathway After Acute Spinal Cord Injury - Wang Xin; Shi Qiang; Ding Jianing; Liang Jiaming; Lin Fangqi; Cai Bin; Chen Yuanyuan; Zhang Guowang; Xu Jianguang; Lian Xiaofeng (Molecular Neurobiology, 2025)

Kill two birds with one stone: Biochar immobilised polydopamine coated compound bacterial agent for remediation of dibutyl phthalate contaminated soil - Yue Tao; Jiaming Xu; Ang Li; Zhao Jiang; Ningyuan Ma; Rui Sun; Ying Zhang (Environmental Research, 2025)

Leveraging machine learning to explore nonlinear associations between urban heat vulnerability and morbidity risk - Jiaming Yang; Zhaomin Tong; Jiwei Xu; Rui An; Yanfang Liu; Yaolin Liu (Urban Climate, 2025)

Efficient Removal of Cr(VI) by Bamboo-Derived Biochar Supported Nano Zero-Valent Iron: Insights into Performance and Mechanism - Yiqun Xu; Jiaming Guo; Siqi Wen; Xiaoyu Shi; Yunlong Zhu; Jianbing Lu; Yang Gao; Mingjuan Zhang; Wenjing Xue (Water, Air, & Soil Pollution, 2025)

Anti-PD-L1 blockade facilitates antitumor effects of radiofrequency ablation by improving tumor immune microenvironment in hepatocellular carcinoma - Jiahua Liang; Mingjian Ma; Wei Feng; Qiongcong Xu; Dong Chen; Jiaming Lai; Jiancong Chen (Apoptosis, 2025)

Effect of heat treatment on the stability of ultrasound-assisted cross-linked myofibrillar protein-stabilized emulsion filler phases via rheology and tribology - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Qi Wang; Zhen Li; Jingyu Wang; Xinglian Xu (Food Hydrocolloids, 2025)

The impact of short-term exposure to criteria air pollutants on sleep disturbance among young adults: A nationwide analysis in 261 Chinese cities - Chunliang Wang; Kai Su; Linming Hu; Xinjie Dai; Xixian Fang; Chunhui Yang; Ruitong Zhang; Jiaming Liu; Junteng Zhou; Chenyu Xu; Hualu Gan; Lingyan Chen; et al. (Environmental Research, 2025)

Mechanistic insights into the hydrogel-supported catalyst for superior oxygen evolution performance - Yuxuan Wei; Lingling Xu; Kefan Shi; Hanwen Gong; Jiaming Hu; Xianghao Zhang; Meilan Pan; Edison Huixiang Ang (Chemical Engineering Journal, 2025)

Calibration of the Solar X-ray Detector on-board the Macao Science Satellite-1B for Soft X-ray Detection - Man-Hei Ng; Xiaoping Zhang; Jianwu Chen; Yongqiang Shi; Fuchang Zuo; Wenxi Peng; Weichun Fu; Liansheng Li; Pengwei Luo; Chi-Long Tang; Guozheng Zhang; Zhiwu Mei; et al. (Science China Earth Sciences, 2025)

Mapping QTLs for stigma exsertion-related traits in two sets of CSSL populations of Oryza sativa cultivars using RSTEP-LRT method - Chunyu Jing; Mei Hai; Jiaming Shen; Xinru Li; Mengyuan Zhang; Changmin Hu; Qing Xu; Jianhua Jiang; Xiaojing Dang (Euphytica, 2025)

Development of a portable multi-step microfluidic device for point-of-care nucleic acid diagnostics - Lulu Shi; Zirui Pang; Jianghao Yu; Jiaming Zhu; Xiaohong Xie; Shiling Xie; Lichuan Gu; Wei Hu; Hai Xu; Ling Li; Jifang Tao; Mingyu Wang (Analytica Chimica Acta, 2025)

Integrating UAV, UGV and UAV-UGV collaboration in future industrialized agriculture: Analysis, opportunities and challenges - Zhigang Ren; Han Zheng; Jian Chen; Tao Chen; Pengyang Xie; Yunzhe Xu; Jiaming Deng; Huanzhe Wang; Mingjiang Sun; Wenchi Jiao (Computers and Electronics in Agriculture, 2024)

The impact of Neoporphyra haitanensis dietary supplement on astaxanthin esters and fatty acids accumulation associated with immune promotion in Pacific white shrimp (Litopenaeus vannamei) - Qian Shen; Shuang Li; Shuyu Zhang; Jiaming Xu; Haimin Chen; Qijun Luo; Rui Yang; Juanjuan Chen (Aquaculture, 2024)

Can wood harvest followed by forest regrowth enhance carbon sequestration of the forest sector in China? - Mengyu Wang; Chao Yue; Junhao He; Pengyi Zhang; Mengyang Xu; Yu Li; Jiaming Wang; Lele Wang; Can Xu (Global and Planetary Change, 2024)

SbSeI for high-efficient photocatalytic degradation of multiple pollutants - Kang Li; Yue Gao; Zhongxin Dong; Huibo Zhang; Xudong Fan; Lei Xu; Jie Huang; Feng Teng; Haibo Fan; Jiaming Song; Chunmei Zhang; Xuexia He; et al. (Environmental Research, 2024)

High efficiency removal of antibiotic resistance gene with designer zinc-finger protein - Jianghao Yu; Meng Fang; Lulu Shi; Jiaming Zhu; Chengzhang Fu; Youming Zhang; Hai Xu; Ling Li; Yu Shen; Mingyu Wang (Bioresource Technology, 2024)

Whole genome sequencing and analysis of Bacillus sp. TTMP2, a tetramethylpyrazine-producing bacterium - Shanling Gan; Lingru Ruan; Xinyi Xu; Lirong Luo; Yu Huo; Jiaming Jiang; Xiumin Zhang; Changhua Shang (Molecular Biology Reports, 2024)

Effects of elevated ozone, warming, and their interactions on the stem lodging resistance of rice under fully open-field conditions - Zaisheng Shao; Jiaming Gu; Longxin He; Yansen Xu; Bo Shang; Zhaozhong Feng (Agriculture, Ecosystems & Environment, 2024)

Construction of La1−xSrxNiO3/g-C3N4 type-Z heterojunctions with enhanced visible-light photocatalytic degradation of organic pollutants - Pengke Yu; Jiaxing Guo; Liang Guo; Yaqin Deng; Juntao Tan; Qunang Xu; Qingmao Zhang; Jiaming Li (Environmental Research, 2024)

Corrigendum to “Implanted 3D gelatin microcryogel enables low-dose cell therapy for osteoarthritis by preserving the viability and function of umbilical cord MSCs” [Chem. Eng. J. 416 (2021) 129140] - Xiaoguang Zhang; Shaokai Liu; Zhenxing Wang; Chao Luo; Zhipeng Dai; Jiaming Sun; Yong Liu; Zengwu Shao; Shuhua Yang; Hui Wang; Juan Wang; Wei Chen; et al. (Chemical Engineering Journal, 2024)

Building block design of thermally regenerable metal–organic framework composites for highly selective lithium adsorption - Xinyu Zhang; Xu Wu; Jiaming Gan; Xin Yu; Huanting Wang; Ranwen Ou (Chemical Engineering Journal, 2024)

Carbonate system in the subtropical Jiulong River Estuary and CO2 flux estimation under modulation of tidal cycle - Weicong Chen; Heng Sun; Zhongyong Gao; Jiaming Lin; Min Xu; Aijun Wang; Shuqin Tao (Acta Oceanologica Sinica, 2024)

Unmanned Surface Vessel–Unmanned Aerial Vehicle Cooperative Path Following Based on a Predictive Line of Sight Guidance Law - Hugan Zhang; Jiaming Fan; Xianku Zhang; Haitong Xu; C. Guedes Soares (Journal of Marine Science and Engineering, 2024)
This paper explores the cooperative control of unmanned surface vessels (USVs) and unmanned aerial vehicles (UAVs) in maritime rescue and coastal surveillance. The USV-UAV system faces challenges of disturbances and substantial inertia-induced overshooting during path following. A novel position prediction line of sight (LOS) guidance law is proposed to address these issues for USV path following control. Radial basis function-based neural networks (RBF-NNs) are used to estimate disturbances, and a high-order differentiator is used to design a velocity observer for unknown USV velocity. The UAV control system employs proportional–derivative (PD) control with feedforward compensation for quadrotor control design and utilizes a finite-time converging third-order differentiator to differentiate non-continuous functions. The simulation results demonstrate strong robustness in the proposed USV-UAV cooperative control algorithm. It achieves path following control in the presence of wind and wave disturbances and exhibits minimal overshoot.

Online sorting of surface defective walnuts based on deep learning - Jingwei Wang; Xiaopeng Bai; Daochun Xu; Wenbin Li; Siyuan Tong; Jiaming Zhang (Journal of Food Engineering, 2024)

A novel sunflower-like nanocarrier based on dual milk-derived proteins for improved bio-accessibility, stability and antioxidant activity of anthocyanin - Shuangshuang Wang; Yi Ding; Liqing Xu; Jiaming Li; Minghui Zhang; Qisheng Hu; Haiyan Wang; Jiaying Zhang; Lili Zhao; Jing Zhang; Wupeng Ge (Food Hydrocolloids, 2024)

Evaluation of a novel attapulgite loaded sulfidized nanoscale zero-valent iron for immobilization of Pb in sediment: Performance, microenvironmental response, and mechanisms - Siqi Wen; Weilong Lin; Qi He; Yiqun Xu; Xiaoyu Shi; Jiaming Guo; Yang Gao; Wenjing Xue (Chemical Engineering Journal, 2024)

Significantly enhancing high-temperature piezoelectric response and Tdr of BF-BT-based ceramics through multi-component optimization strategy - Huabin Yang; Jiaming Zhu; Xueting Wang; Qiuling Luo; Hua Tan; Haibo Zhang; Jiwen Xu; Qiaohong Chen (Chemical Engineering Journal, 2024)

The New Roles of traf6 Gene Involved in the Development of Zebrafish Liver and Gonads - Hongyan Xu; Wenzhuo Ban; Jiaming Tian; Jianfei Xu; Zhimin Tan; Sendong Li; Kaili Chen; Mi Ou; Kaibin Li (Marine Biotechnology, 2024)

Amino-modified biochar-supported S-nZVI for Cr(VI) and total Cr removal from water: Parameter regulation, kinetic and mechanistic analysis - Yiqun Xu; Jiaming Guo; Siqi Wen; Xiaoyu Shi; Qi He; Weilong Lin; Yu Wang; Yang Gao; Rongzhong Wang; Wenjing Xue (Journal of Water Process Engineering, 2024)

A new paradigm for construction safety management in China: Introducing knowledge graph and accident database into the early-stage of BIM - Wangxin Li; Ping Wu; Jiaming Huang; Yidong Xu (Journal of Cleaner Production, 2024)

Application of rheology and interfacial rheology to investigate the emulsion stability of ultrasound-assisted cross-linked myofibrillar protein: Effects of oil phase types - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Weiyi Zhang; Xinglian Xu (Food Hydrocolloids, 2024)

Erratum to: Low-intensity pulsed ultrasound ameliorates angiotensin II-induced cardiac fibrosis by alleviating inflammation via a caveolin-1-dependent pathway - Kun Zhao; Jing Zhang; Tianhua Xu; Chuanxi Yang; Liqing Weng; Tingting Wu; Xiaoguang Wu; Jiaming Miao; Xiasheng Guo; Juan Tu; Dong Zhang; Bin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

Suspended sediment-discharge hysteresis characteristics and controlling factors in a small watershed of southern China - Yu Long; Ming Lei; Taoxi Li; Peiyao Xiao; Siyuan Liu; Jiaming Xu; Fang Tang; Xuexiang Hu; Xizhong Hu; Xiaodong Nie; Zhongwu Li; Yaojun Liu (CATENA, 2024)

Memristive switching in the surface of a charge–density–wave topological semimetal - Jianwen Ma; Xianghao Meng; Binhua Zhang; Yuxiang Wang; Yicheng Mou; Wenting Lin; Yannan Dai; Luqiu Chen; Haonan Wang; Haoqi Wu; Jiaming Gu; Jiayu Wang; et al. (Science Bulletin, 2024)

Contributions of China's terrestrial ecosystem carbon uptakes to offsetting CO2 emissions under different scenarios over 2001–2060 - Mengyang Xu; Ziyu Zhang; Chao Yue; Jie Zhao; Pengyi Zhang; Mengyu Wang; Jiaming Wang; Hongfei Zhao; Jinyue Liu; Xianhui Tang; Junhao He (Global and Planetary Change, 2024)

Development of CaCl2·6H2O-mannitol/SiO2 shape-stabilized composite phase change material for the radiant cooling panel system - Jiaming Zhang; Haiwen Li; Yanliang Du; Tao Xu; Ting Zou; Shen Wei; Dongqiao Zhang (Energy and Buildings, 2024)

Rab18 maintains homeostasis of subcutaneous adipose tissue to prevent obesity-induced metabolic disorders - Jiaming Liu; Liangkui Li; Dijin Xu; Yuqi Li; Tao Chen; Yeyang Liu; Yuqian Bao; Yan Wang; Longyan Yang; Peng Li; Li Xu (Science China Life Sciences, 2024)

Transporters and phytohormones analysis reveals differential regulation of ryegrass (Lolium perenne L.) in response to cadmium and arsenic stresses - Wenwen Li; Jie Li; Khateeb Hussain; Kaihao Peng; Jiaming Yu; Miaoqing Xu; Shiyong Yang (Journal of Hazardous Materials, 2024)

High performance self-assembled sulfidized nanoscale zero-valent iron for the immobilization of cadmium in contaminated sediments: Optimization, microbial response, and mechanisms - Yiqun Xu; Hongdou Liu; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Qi He; Weilong Lin; Yang Gao; Rongzhong Wang; Wenjing Xue (Journal of Hazardous Materials, 2024)

Clustering and optimization of nodes, beams and panels for cost-effective fabrication of free-form surfaces - Minghao Bi; Yuanpeng Liu; Tao Xu; Yunzhen He; Jiaming Ma; Zicheng Zhuang; Yi Min Xie (Engineering Structures, 2024)

Biochanin a ameliorates DSS-induced ulcerative colitis by improving colonic barrier function and protects against the development of spontaneous colitis in the Muc2 deficient mice - Haina Zhang; Xueqi Wang; Linxian Zhao; Kai Zhang; Jiaming Cui; Guangmeng Xu (Chemico-Biological Interactions, 2024)

Affecting factors and mechanism of removing antibiotics and antibiotic resistance genes by nano zero-valent iron (nZVI) and modified nZVI: A critical review - Wenjing Xue; Xiaoyu Shi; Jiaming Guo; Siqi Wen; Weilong Lin; Qi He; Yang Gao; Rongzhong Wang; Yiqun Xu (Water Research, 2024)

Zinc saponite protection layer with fast zinc-ion transfer kinetics to enable highly reversible Zn anode - Jiaming Li; Hanhao Liang; Jian Wu; Jiancheng Xu; Yini Long; Jianglin Wang; Zhanhong Yang (Chemical Engineering Journal, 2024)

EEGNet-based multi-source domain filter for BCI transfer learning - Mengfan Li; Jundi Li; Zhiyong Song; Haodong Deng; Jiaming Xu; Guizhi Xu; Wenzhe Liao (Medical & Biological Engineering & Computing, 2024)

Molecular Determinants of Neurocognitive Deficits in Glioma: Based on 2021 WHO Classification - Kun Zhang; Tianrui Yang; Yu Xia; Xiaopeng Guo; Wenlin Chen; Lijun Wang; Junlin Li; Jiaming Wu; Zhiyuan Xiao; Xin Zhang; Wenwen Jiang; Dongrui Xu; et al. (Journal of Molecular Neuroscience, 2024)
Cognitive impairment is a common feature among patients with diffuse glioma. The objective of the study is to investigate the relationship between preoperative cognitive function and clinical as well as molecular factors, firstly based on the new 2021 World Health Organization’s updated classification of central nervous system tumors. A total of 110 diffuse glioma patients enrolled underwent preoperative cognitive assessments using the Mini-Mental State Examination and Montreal Cognitive Assessment. Clinical information was collected from medical records, and gene sequencing was performed to analyze the 18 most influenced genes. The differences in cognitive function between patients with and without glioblastoma were compared under both the 2016 and 2021 WHO classification of tumors of the central nervous system to assess their effect of differentiation on cognition. The study found that age, tumor location, and glioblastoma had significant differences in cognitive function. Several genetic alterations were significantly correlated with cognition. Especially, IDH , CIC , and ATRX are positively correlated with several cognitive domains, while most other genes are negatively correlated. For most focused genes, patients with a low number of genetic alterations tended to have better cognitive function. Our study suggested that, in addition to clinical characteristics such as age, histological type, and tumor location, molecular characteristics play a crucial role in cognitive function. Further research into the mechanisms by which tumors affect brain function is expected to enhance the quality of life for glioma patients. This study highlights the importance of considering both clinical and molecular factors in the management of glioma patients to improve cognitive outcomes.

Activation of persulfate by biochar-supported sulfidized nanoscale zero-valent iron for degradation of ciprofloxacin in aqueous solution: process optimization and degradation pathway - Wenjing Xue; Xinyu Chen; Hongdou Liu; Jun Li; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Yang Gao; Rongzhong Wang; Yiqun Xu (Environmental Science and Pollution Research, 2024)

Taurochenodeoxycholic acid exerts anti-viral activities upon SGIV infection via anti-inflammatory response - Fengyi Zhu; Weihua Xu; Wenji Wang; Jiaming Liao; Youhua Huang; Xiaohong Huang; Qiwei Qin (Aquaculture, 2024)

Exploring the relationship between the interfacial properties and emulsion properties of ultrasound-assisted cross-linked myofibrillar protein - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Zongyun Yang; Xinglian Xu (Food Hydrocolloids, 2024)

Enhanced immobilization of cadmium in contaminated paddy soil by biochar-supported sulfidized nanoscale zero-valent iron - Yiqun Xu; Shan Cao; Xinyu Chen; Jun Li; Hongdou Liu; Yang Gao; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Wenjing Xue (Journal of Soils and Sediments, 2024)

Occurrence and fate of antibiotics and ARGs in a wastewater treatment plant with JHB process in Guangzhou, South China: Removal performance, interaction and host analysis - Yuepeng Deng; Huaihao Xu; Yuting Gu; Yongyin Lan; Junpeng Diao; Zhijian Xiao; Jiaming Zhu; Biqing Li; Jie Zou; Kaoming Zhang; Yuxian Liu; Jingchuan Xue; et al. (Journal of Water Process Engineering, 2023)

A shining transmutation of lignin into multicolor carbon dots via the dynamic solvent-fractionation engineering - Xinyan Hou; Jikun Xu; Pengfei Zhou; Lin Dai; Jiaming Zhang; Xiao Xiao; Kaifu Huo (Chemical Engineering Journal, 2023)

Spatiotemporal distribution of phytoplankton community structure and its relationship with environmental factors in Hongze Lake, China - Jiahui Shi; Lixiao Ni; Jiaming Liu; Chen Xu; Jianhua Zhang; Xuqing Chen (Urban Climate, 2023)

Exploring year-to-year spatiotemporal changes in cycling patterns for bike-sharing system in the pre-, during and post-pandemic periods - Xiaoying Shi; Junjie Zhao; Jiaming He; Haitao Xu (Sustainable Cities and Society, 2023)

Thermal-and-mechanochemical recycling of waste polypropylene into maleated-epoxided degradation products as warm-mix asphalt modifier: Performance improvement and production mechanism analysis - Xiong Xu; Yaming Chu; Yi Luo; Yuhao Peng; Nannan Yang; Jiaming Yan; Xuyong Chen; Fuliao Zou; Anand Sreeram (Journal of Cleaner Production, 2023)

Immobilization of cadmium in river sediments by different modified nanoscale zero-valent iron: performance, mechanisms, and Fe dissolution - Wenjing Xue; Hongdou Liu; Jun Li; Xinyu Chen; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Shan Cao; Yang Gao; Rongzhong Wang; Yiqun Xu (Environmental Science and Pollution Research, 2023)

Electro-enhanced metal-free peroxymonosulfate activator coupled with membrane-assisted process for simultaneous Ni-EDTA decomplexation and Ni ions recovery - Jiaming Zhang; Chao Yu; Longqian Xu; Zhenyu Zhao; Deli Wu (Chemosphere, 2023)

A multi-scale experiment analysis of air entrainment and heat exhaust coefficient under lateral smoke exhaust in tunnel fires - Qiulin Liu; Zhisheng Xu; Chuangang Fan; Xiaochun Zhang; Jiaming Zhao; Houlin Ying; Haowen Tao (Tunnelling and Underground Space Technology, 2023)

Multi-objective shape optimization of autonomous underwater vehicle by coupling CFD simulation with genetic algorithm - Xiaodong Chen; Liang Yu; Leo Yang Liu; Lele Yang; Shunyuan Xu; Jiaming Wu (Ocean Engineering, 2023)

Seismic response analysis of submerged floating tunnel considering non-uniform excitation and flexible-support boundary effect - Jiaming Xie; Jing Li; Jianyun Chen; Qiang Xu (Ocean Engineering, 2023)

Isolation and identification of a megalocytivirus strain (SKIV-TJ) from cultured spotted knifejaw (Oplegnathus punctatus) in China and its pathogenicity analysis - Jiaming Liao; Shaozhu Kang; Luhao Zhang; Dongzhuo Zhang; Zhuqing Xu; Qiwei Qin; Jingguang Wei (Fish & Shellfish Immunology, 2023)

Recent advances in sulfidized nanoscale zero-valent iron materials for environmental remediation and challenges - Wenjing Xue; Jun Li; Xinyu Chen; Hongdou Liu; Siqi Wen; Xiaoyu Shi; Jiaming Guo; Yang Gao; Jian Xu; Yiqun Xu (Environmental Science and Pollution Research, 2023)

Full-scale experimental study on evacuation behavior characteristics of underwater road tunnel with evacuation stairs under blocked conditions - Kunkun Chu; Baochao Xie; Zhisheng Xu; Dan Zhou; Lu He; Jiaming Zhao; Houlin Ying (Tunnelling and Underground Space Technology, 2023)

Self-powered health monitoring with ultrafast response and recovery enabled by nanostructured silicon moisture-electric generator - Yuhang Song; Chang Shu; Zheheng Song; Xuelian Zeng; Xianrong Yuan; Yanan Wang; Jiaming Xu; Qianyue Feng; Tao Song; Beibei Shao; Yusheng Wang; Baoquan Sun (Chemical Engineering Journal, 2023)

Establishment and characterization of a brain tissue cell line from spotted knifejaw ( Oplegnathus punctatus ) and its susceptibility to several fish viruses - Jiaming Liao; Xin Zhang; Shaozhu Kang; Luhao Zhang; Dongzhuo Zhang; Zhuqing Xu; Qiwei Qin; Jingguang Wei (Journal of Fish Diseases, 2023)
Cells are important in the study of virus isolation and identification, viral pathogenic mechanisms and antiviral immunity. The spotted knifejaw ( Oplegnathus punctatus ) is a significant farmed fish in China that has been greatly affected by diseases in recent years. In this study, a new cell line derived from the spotted knifejaw brain (SKB) was established and characterized. SKB cells multiplied well in Leibovitz's L‐15 medium supplemented with 10% fetal bovine serum at 28°C. Chromosome analysis revealed that modal chromosome number was 48 for SKB. SKB cells exhibit susceptibility to several fish viruses, such as a largemouth bass virus, red grouper nervous necrosis virus (RGNNV), infectious spleen and kidney necrosis virus (ISKNV), Singapore grouper iridovirus (SGIV) and spotted knifejaw iridovirus isolate (SKIV‐TJ), as shown by cytopathic effect and increased viral titers. Electron microscopy results showed that the cytoplasm contained a large number of vacuoles, and many virus particles existed at the edge of the vacuoles in RGNNV‐infected cells and numerous viral particles were scattered throughout the cytoplasm in both ISKNV‐ and SKIV‐TJ‐infected cells. These results suggest that SKB is an ideal tool for studying host–virus interactions and potential vaccine development.

Effects of Dietary Lentinus edodes Fermentation Supplementation on Digestive Enzyme Activity, Antioxidant Capacity and Morphology of the Liver and Intestine in Largemouth Bass (Micropterus salmoides) Fed High Plant Protein Diets - Jiaming Xu; Zhoulin Yu; Guangye Liu; Sijie Li; Guoyong Zhou; Hanhua Wang; Yewei Dong; Cuihong You; Weidong Bai; Meng Zhou; Yanhua Huang; Xiaohong Tan (Fishes, 2023)
This study evaluated the effect of Lentinus edodes fermentation (LEF) on digestive enzyme activity, antioxidant capacity and morphology of the liver and intestine in largemouth bass (Micropterus salmoides) fed high plant protein diets (HPPD). LEF was supplemented in HPPD with 0 g kg−1 (LEF0), 10 g kg−1 (LEF1), 20 g kg−1 (LEF2), 30 g kg−1 (LEF3), 40 g kg−1 (LEF4), 50 g kg−1 (LEF5), respectively, and then the six diets were fed to largemouth bass with a body weight of 28.8 ± 0.05 g for eight weeks. Juvenile fish were randomized into 6 groups and each group had 4 replicates with 40 fish. Dietary LEF supplementation alleviated the liver inflammatory reaction of largemouth bass caused by HPPD and improved liver morphology. Goblet cells multiplied and the gut muscle layer thickened after LEF supplementation. The LEF significantly increased amylase activity in the liver and intestine of largemouth bass in individual experimental groups. The LEF could increase the activity of catalase in the liver and intestine of largemouth bass (p

Magnetic nanometer combined with microwave: Novel rapid thawing promotes phenolics release in frozen-storage lychee - Canhua Xu; Jiaming Lu; Qingzhu Zeng; Junjia Zhang; Lihong Dong; Fei Huang; Yingbin Shen; Dongxiao Su (Food Chemistry, 2023)

From black water to flushing water: potential applications of chlorine-mediated indirect electrooxidation for ammonia removal - Shanshan Liu; Longqian Xu; Xiaoqing Lin; Jiaming Zhang; Deli Wu (Environmental Science and Pollution Research, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A minimal genome design to maximally guarantee fertile inter-subspecific hybrid rice - Penghui Zhou; Zhengji Wang; Xingchen Zhu; Yao Tang; Liang Ye; Huihui Yu; Yating Li; Ningke Zhang; Ting Liu; Tian Wang; Yuying Wu; Dengyun Cao; et al. (Molecular Plant, 2023)

An improved spatial case-based reasoning considering multiple spatial drivers of geographic events and its application in landslide susceptibility mapping - Zheng Zhao; Jianhua Chen; Jiaming Yao; Kaihang Xu; Yangyang Liao; Huawei Xie; Xianxia Gan (CATENA, 2023)

Selection and truncation of aptamers as fluorescence sensing platforms for selective and sensitive detection of nitrofurazone - Xu Wen; Xueling Yan; Xiaoling Zheng; Qiming Kou; Lulan Yang; Jiaming Tang; Xingyue Chen; Yong Xie; Tao Le (Analytica Chimica Acta, 2023)

Light use efficiency models incorporating diffuse radiation impacts for simulating terrestrial ecosystem gross primary productivity: A global comparison - Hang Xu; Zhiqiang Zhang; Xiaoyun Wu; Jiaming Wan (Agricultural and Forest Meteorology, 2023)

Evaluation of intervention effects of dietary coenzyme Q10 supplementation on oxidized fish oil-induced stress response in largemouth bass Micropterus salmoides - Yuexing Zhang; Linwei Cai; Zhiyong Dong; Bowen Wu; Yangyang Gong; Baoping Zhang; Bo Wang; Jiaming Kang; Tianhong Ke; Zhijin Xu; Trond Storebakken; Bo Shi (Fish & Shellfish Immunology, 2023)

Spatiotemporal patterns of fire-driven forest mortality in China - Jie Zhao; Jiaming Wang; Yifan Meng; Ziqiang Du; Hui Ma; Linghua Qiu; Qi Tian; Liang Wang; Mengyang Xu; Hongfei Zhao; Chao Yue (Forest Ecology and Management, 2023)

Highly efficient removal of hexavalent chromium from electroplating wastewater by ferrous/ferric hydroxide complex: From lab-scale to pilot-scale study - Xiaoqing Lin; Longqian Xu; Zhenyu Zhao; Shanshan Liu; Jiaming Zhang; Deli Wu (Chemical Engineering Journal, 2023)

Chemical constituents from the leaves of psidium guajava linn. and their chemotaxonomic significance - Guangxin Zhou; Jiaming Zhao; Chang Gong; Jixuan Xu; Ce Song; Dali Meng (Natural Product Research, 2023)

Inspired by philosophizing of “point to area”: Ion pre-intercalation induces the reconstitution of interlayer environment of MXene for lithium storage - Miao Liu; Xin Qu; Yixuan Wang; Yukai Zhang; Cuimei Zhao; Bo Liu; Xiangxin Xue; Junkai Zhang; Zhao Wang; Jiaming Li; Wenjuan Han; Shichong Xu; et al. (Chemical Engineering Journal, 2023)

Lanthanum-modified polydopamine loaded Acinetobacter lwoffii DNS32 for phosphate and atrazine removal: Insights into co-adsorption and biodegradation mechanisms - Siyue Han; Yue Tao; Yunhe Cui; Jiaming Xu; Hanxun Ju; Linlin Fan; Lin Zhang; Ying Zhang (Bioresource Technology, 2023)

Mechanisms of PiT2-loop7 Missense Mutations Induced Pi Dyshomeostasis - Hao Sun; Xuan Xu; Junyu Luo; Tingbin Ma; Jiaming Cui; Mugen Liu; Bo Xiong; Shujia Zhu; Jing-Yu Liu (Neuroscience Bulletin, 2023)

Microbially driven fate of terrigenous particulate organic matter in oceans - Lianbao Zhang; Mingming Chen; Yue Zheng; Jianning Wang; Xilin Xiao; Xiaowei Chen; Chen Hu; Jiaming Shen; Jihua Liu; Kai Tang; Dapeng Xu; Qiang Shi; et al. (Limnology and Oceanography, 2023)
A long‐standing enigma in oceanography is why terrestrial organic matter is “missing” in the global ocean, despite the considerable discharge into it every year. Although some explanations, such as mineralogical composition, hydrodynamic processes, and priming effect, have been proposed, we hypothesize that the essential mechanism behind the missing organic matter is microbial processing, for which the underlying coupled geochemical, molecular, and genetic evidence is unknown. An ultra‐large‐volume, long‐term river–seawater stratified simulation system was constructed to unravel the microbially driven fate of terrigenous particulate organic matter (POM) in oceans. Analysis of combining the molecular with POM chemical composition data suggests that Bacteroidetes could act as pioneers in the processing of terrigenous POM in oceans, degrading high‐molecular‐weight, high‐carbon compounds such as polysaccharides. Remaining low‐molecular‐weight nitrogenous organic matter is subsequently degraded by Planctomycetes and Proteobacteria. Isotopic signals show that this preferential degradation causes a distinct “aging” effect of POM, and along with nitrification enhanced by remineralization, causes a decrease in the POM C : N ratio. Degradation of terrigenous POM and bacterial biomass biosynthesis leads to positive deviations in δ 15 N and δ 13 C. Relatively refractory hydrocarbons, aromatic compounds, and phenols are accumulated by microbial processes in this system. This study provides mechanistic insights into the missing chemical and isotopic signals and microbially driven fate of terrigenous POM in the ocean, with important implications for how riverine material input affects marine carbon and nitrogen cycling.

Simulations of sea fog case impacted by air–sea interaction over South China Sea - Liguo Han; Shuqin Zhang; Feng Xu; Jingjing Lü; Zebin Lu; Guiling Ye; Siqi Chen; Jianjun Xu; Jiaming Du (Frontiers in Marine Science, 2022)
A sea fog event in the South China Sea was simulated using a coupled ocean–atmosphere model (WRF for the atmosphere and ROMS for the ocean). Offshore and onshore visibility, liquid water content, air temperature, humidity, and wind speed observations and MICAPS data were utilized to validate the model results. The results of the coupled model were also compared with those of the uncoupled atmosphere model. Sea fog duration in the coupled model was closer to offshore and onshore observations, but the uncoupled model emptily forecasted offshore fog, and underreported onshore fog. Air–sea temperature difference played an important role in regulating the formation and dissipation of sea fog. The decrease of sea surface temperature in the coupled model cooled the low-level atmosphere, promoted the condensation of low-level water vapor, and increased the low-level water vapor. The decrease of air–sea temperature difference strengthened the low-level stable stratification, which weakened the horizontal wind speed and favored the formation and development of sea fog. Rising wind speed was the major driver of fog dissipation.

Relative importance of branching enzyme isoforms in determining starch fine structure and physicochemical properties of indica rice - Piengtawan Tappiban; Yaqi Hu; Jiaming Deng; Jiajia Zhao; Yining Ying; Zhongwei Zhang; Feifei Xu; Jinsong Bao (Plant Molecular Biology, 2022)

NoiD, a DedA membrane protein required for homeostasis maintaining of Rhizobium leguminosarum biovar viciae during symbiosis with Pisum sativum - Xiaofang Li; Jiaming Xu; Yajuan Wei; Zirui Chen (Symbiosis, 2022)

Human Bone Marrow Mesenchymal Stem Cell–Derived Exosomes Attenuate Blood–Spinal Cord Barrier Disruption via the TIMP2/MMP Pathway After Acute Spinal Cord Injury - Wang Xin; Shi Qiang; Ding Jianing; Liang Jiaming; Lin Fangqi; Cai Bin; Chen Yuanyuan; Zhang Guowang; Xu Jianguang; Lian Xiaofeng (Molecular Neurobiology, 2021)

Low-intensity pulsed ultrasound ameliorates angiotensin II-induced cardiac fibrosis by alleviating inflammation via a caveolin-1-dependent pathway - Kun Zhao; Jing Zhang; Tianhua Xu; Chuanxi Yang; Liqing Weng; Tingting Wu; Xiaoguang Wu; Jiaming Miao; Xiasheng Guo; Juan Tu; Dong Zhang; Bin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2021)

A study on the effects of anion, cation, organic compounds, and pH on the release behaviors of As and Sb from sediments - Haibo Wang; Jiaming Xu; Mario Alberto Gomez; Zhongliang Shi; Yongfeng Jia (Environmental Science and Pollution Research, 2021)

Thrust Characteristics of Ducted Propeller and Hydrodynamics of an Underwater Vehicle in Control Motions - Jiaming Wu; Yizhe Dou; Haiyan Lv; Chenghua Ma; Le Zhong; Shunyuan Xu; Xiangxi Han (Journal of Marine Science and Engineering, 2021)
A numerical technique to simulate the hydrodynamic behavior of ducted propellers attached to an underwater vehicle traveling under the mutually interacting flow fields of the vehicle and the propellers is proposed; the hydrodynamic performance of the propellers and the hydrodynamic loading on the main body of the vehicle when it is in different kinds of motion is investigated numerically. In the research, 3D geometric models of the duct, propeller, and main body of the vehicle are first constructed according to their geometrical features. A computational fluid dynamics (CFD) technique based on the hybrid algorithm of dynamic mesh-nested sliding mesh is applied to solve the Navier–Stokes equations that govern the fluid motion around the duct, propeller, and main body of the vehicle when it is in motion. These equations are solved numerically with the CFD code Fluent. With the proposed numerical simulation technique, the hydrodynamic characteristics of the thrusts generated by the ducted propellers and the loading on the main body in the vehicle system under the mutually interacting flow fields are observed. The results of our numerical simulation indicate that the hybrid algorithm of dynamic mesh-nested sliding mesh can simulate multiple degrees of freedom of motion in underwater vehicle systems. In different motion states, the main body exerts a significant influence on the investigated flow fields; during the vehicle motions, negative wakes are formed on both sides of the main body, which lead to a decrease in the thrusts generated by the propellers on both sides. The thrust of the middle propeller is greater than that of the normal single one because of the obstructing effect in the tunnel caused by the main body.

Mapping of a major QTL for salinity tolerance at the bud burst stage in rice (Oryza sativa L) using a high-density genetic map - Lei Lei; Zhenghong Han; Bowen Cui; Luomiao Yang; Hualong Liu; Jingguo Wang; Hongwei Zhao; Wei Xin; Xianwei Li; Jiaming Li; Jingnan Cui; Shanbin Xu; et al. (Euphytica, 2021)

Role of rgsA in Oxidative Stress Resistance in Pseudomonas aeruginosa - Shuyi Hou; Jiaqin Zhang; Xiaobo Ma; Qiang Hong; Lili Fang; Gangsen Zheng; Jiaming Huang; Yingchun Gao; Qiaoli Xu; Xinguo Zhuang; Xiuyu Song (Current Microbiology, 2021)

Maneuverability and Hydrodynamics of a Tethered Underwater Robot Based on Mixing Grid Technique - Jiaming Wu; Shunyuan Xu; Hua Liao; Chenghua Ma; Xianyuan Yang; Haotian Wang; Tian Zhang; Xiangxi Han (Journal of Marine Science and Engineering, 2021)
The maneuverability and hydrodynamic performance of the tethered underwater robot in a uniform flow field is investigated. In this research, a tethered underwater robot symmetrically installed with NACA66 hydrofoils and Ka 4-70/19A ducted propellers around its main body is first constructed. The method of overlapping grid combined with sliding mesh is applied in the numerical simulations, and the principle of relative motion is adopted to describe the hydrodynamic responses of the tethered underwater robot during the robot manipulation. The reliability of the CFD methods applied in this research is verified by experimental results, and the comparison between numerical and experimental ones shows that there is very little difference being found. The numerical results indicate that computational cost due to the research’s large-scale domain can be effectively reduced by the adopted numerical methods, hydrofoils’ control effect is greatly influenced by the towing speeds, and thrusts issued from the ducted propellers are related to the tethered underwater robot’s position and towing speed.

Canopy photosynthetic capacity drives contrasting age dynamics of resource use efficiencies between mature temperate evergreen and deciduous forests - Hang Xu; Jingfeng Xiao; Zhiqiang Zhang; Scott V. Ollinger; David Y. Hollinger; Yude Pan; Jiaming Wan (Global Change Biology, 2020)
Forest resource use efficiencies (RUEs) can vary with tree age, but the nature of these trends and their underlying mechanisms are not well understood. Understanding the age dynamics of forest RUEs and their drivers is vital for assessing the trade‐offs between forest functions and resource consumption, making rational management policy, and projecting ecosystem carbon dynamics. Here we used the FLUXNET2015 and AmeriFlux datasets and published literature to explore the age‐dependent variability of forest light use efficiency (LUE) and inherent water use efficiency as well as their main regulatory variables in temperate regions. Our results showed that evergreen forest RUEs initially increased before reaching the mature stage (i.e., around 90 years old), and then gradually declined; in contrast, RUEs continuously increased with age for mature deciduous forests. Changing canopy photosynthetic capacity ( A max ) was the primary cause of age‐related changes in RUEs across temperate forest sites. More importantly, soil nitrogen (N) increased in mature deciduous forests through time but decreased in older evergreen forests. The age‐dependent changes in soil N were closely linked with the age dynamics of A max for mature temperate forests. Additionally, soil nutrient conditions played a greater role in deciduous forest RUEs than evergreen forest RUEs. This study highlights the importance of stand age and forest type on temperate forest RUEs over the long term.

Development and characterization of 33 SNP markers for the red-crowned crane (Grus japonensis) using a genotyping-by-sequencing approach - Nan Xu; Yining Chen; Jiaming Zhang; Qingzheng Zhang; Jing Yang; Jingjing Li; Hongyi Liu (Conservation Genetics Resources, 2020)

Preliminary marine gravity field from HY-2A/GM altimeter data - Qiankun Liu; Ke Xu; Maofei Jiang; Jiaming Wang (Acta Oceanologica Sinica, 2020)

Gene Biomarkers Derived from Clinical Data of Hepatocellular Carcinoma - Jiaming Qi; Jiaxing Zhou; Xu-Qing Tang; Yaolai Wang (Interdisciplinary Sciences: Computational Life Sciences, 2020)

Oxidative Damage Induced by Nano-titanium Dioxide in Rats and Mice: a Systematic Review and Meta-analysis - Hongmei An; Chunmei Ling; Mengchuan Xu; Mingjuan Hu; Haixia Wang; Jiaqing Liu; Guangling Song; Jiaming Liu (Biological Trace Element Research, 2020)

Review of CRISPR/Cas9 sgRNA Design Tools - Yingbo Cui; Jiaming Xu; Minxia Cheng; Xiangke Liao; Shaoliang Peng (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Study of physico-mechanical properties of Emeishan basalt saprolites in Yunnan, China - Zhe Ren; Luyue Zhang; Zemin Xu; Jiaming Zhang; Jipu Chen (Bulletin of Engineering Geology and the Environment, 2017)

Chemical and isotopic constrains on the origin of brine and saline groundwater in Hetao plain, Inner Mongolia - Jun Liu; Zongyu Chen; Lijuan Wang; Yilong Zhang; Zhenghong Li; Jiaming Xu; Yurong Peng (Environmental Science and Pollution Research, 2016)

Investigation of the SA evolution by using the CHAOS-4 model over 1997–2013 - JiaMing Ou; AiMin Du; WenYao Xu (Science China Earth Sciences, 2016)

Species distribution, genetic diversity and barcoding in the duckweed family (Lemnaceae) - Yaliang Xu; Shuai Ma; Meng Huang; Ming Peng; Manuela Bog; K. Sowjanya Sree; Klaus-J. Appenroth; Jiaming Zhang (Hydrobiologia, 2015)

In vitro isolation and cultivation of human chondrocytes for osteoarthritis renovation - Jiaming Xu; Changqing Zhang (In Vitro Cellular & Developmental Biology - Animal, 2014)

Propofol Administration Modulates AQP-4 Expression and Brain Edema After Traumatic Brain Injury - Zhongyang Ding; Jiaming Zhang; Jinyu Xu; Guangjie Sheng; Guorong Huang (Cell Biochemistry and Biophysics, 2013)

A high resolution lithospheric magnetic field model over China - JiaMing Ou; AiMin Du; E. Thébault; WenYao Xu; XiaoBo Tian; TieLong Zhang (Science China Earth Sciences, 2013)

Isolation and characterization of a novel EAR-motif-containing gene GmERF4 from soybean (Glycine max L.) - Gaiyun Zhang; Ming Chen; Xueping Chen; Zhaoshi Xu; Liancheng Li; Jiaming Guo; Youzhi Ma (Molecular Biology Reports, 2010)

Evaporite karst and resultant geohazards in China - Lu Yaoru; Zhang Feng’e; Qi Jixiang; Xu Jiaming; Guo Xiuhong (Carbonates and Evaporites, 2002)